Systemic Measures and Legislative and Organizational Frameworks Aimed at Preventing or Mitigating Drug Shortages in 28 European and Western Asian Countries - Bochenek, Tomasz; Abilova, Vafa; Alkan, Ali; Asanin, Bogdan; de Miguel Beriain, Iñigo; Besovic, Zeljka; Vella Bonanno, Patricia; Bucsics, Anna; Davidescu, Michal; De Weerdt, Elfi; Duborija-Kovacevic, Natasa; Fürst, Jurij; et al. (Frontiers in Pharmacology, 2018)
Drug shortages have been identified as a public health problem in an increasing number of countries. This can negatively impact on the quality and efficiency of patient care, as well as contribute to increases in the cost of treatment and the workload of health care providers. Shortages also raise ethical and political issues. The scientific evidence on drug shortages is still scarce, but many lessons can be drawn from cross-country analyses. The objective of this study was to characterize, compare, and evaluate the current systemic measures and legislative and organizational frameworks aimed at preventing or mitigating drug shortages within health care systems across a range of European and Western Asian countries. The study design was retrospective, cross-sectional, descriptive and observational. Information was gathered through a survey distributed among senior personnel from ministries of health, state medicines agencies, local health authorities, other health or pharmaceutical pricing and reimbursement authorities, health insurance companies and academic institutions, with knowledge of the pharmaceutical markets in the 28 countries studied. Our study found that formal definitions of drug shortages currently exist in only a few countries. The characteristics of drug shortages, including their assortment, duration, frequency and dynamics, were found to be variable and sometimes difficult to assess. Numerous information hubs were identified. Providing public access to information on drug shortages to the maximum possible extent is a prerequisite for performing more advanced studies on the problem and identifying solutions. Imposing public service obligations, providing the formal possibility to prescribe unlicensed medicines, and temporary bans on parallel exports are widespread measures. A positive finding of our study was the identification of numerous bottom-up initiatives and organizational frameworks aimed at preventing or mitigating drug shortages. The experiences and lessons drawn from these initiatives should be carefully evaluated, monitored and presented to a wider international audience for careful appraisal. To be able to find solutions to the problem of drug shortages, there is an urgent need to develop a set of agreed definitions for drug shortages, as well as methodologies for their evaluation and monitoring. This is being progressed.